Micro‐morphological characteristics of seed and ovary trichomes of Iranian Glaucium Mill. species (Papaveraceae) and their taxonomic importance. (19th December 2019) - Tavakkoli, Zahra; Assadi, Mostafa
Abstract : Seeds and trichomes of 15 taxa of the genus Glaucium distributed in Iran were examined by light microscopy (LM) and scanning electron microscopy (SEM). The seeds are slightly shiny to rather shiny, however, strongly shiny seeds were also observed in some species ( G. corniculatum and G. grandiflorum ). The basic shape of the seeds is semicircular to reniform, but reniform and elongated reniform seeds were found in G. oxylobum and G. elegans, respectively. The sculpturing of the testa surface are verrucate–rugulate (most frequent type), verrucate–granulate, verrucate–perforate, verrucate–lineolate, rugulate–granulate, rugulate and ocellate. Elongated polygonal epidermal cells dominate in most taxa investigated, but there are polygonal and irregular polygonal cells in a few taxa. The investigated species have two types of trichomes on the ovary: tuberculate and non‐tuberculate. The non‐tuberculate trichomes are of two subtypes: pilose and squamiform. Based on the number of cells, the squamiform trichomes were further divided into two groups (uniseriate and multiseriate) differing in shape, size and cellular structure. The results show that the micro‐morphological characteristics of seed and ovary trichomes provide useful and significant information for separation of species and taxa within species and a diagnostic key to the taxa is provided.